Bimodal microstructure toughens plasma sprayed Al2O3-8YSZ-CNT coatings. Issue 8 (15th April 2023) - Bhadauria, Alok; Bajpai, Shipra; Tiwari, Ashutosh; Mishra, Shiva Kant; Nisar, Ambreen; Dubey, Shruti; Chavan, Nishant; Keshri, Anup K.; Balani, Kantesh
Abstract: Current work pursues generating controlled bimodal microstructure by plasma spraying of micrometer-sized Al2 O3 and nanostructured spray-dried agglomerate with reinforcement of 20 wt% of 8 mol % yttria stabilized zirconia (8YSZ) and 4 wt% carbon nanotube (CNT) as potential thermal barrier coating (TBC) on the Inconel 718 substrate. Composite coatings exhibit bimodal microstructure of: (i) fully melted and resolidified microstructured region (MR), and (ii) partially melted and solid state sintered nanostructured regions (NR). Reinforcement with 8YSZ has led to an increase in hardness from ∼12.8 GPa (for μ-Al2 O3 ) to ∼13.9 GPa in MR of reinforced Al2 O3 -YSZ composite. Further, with the addition of CNT in Al2 O3 -8YSZ reinforced composite, hardness of MR has remained similar ∼13.9 GPa (8YSZ reinforced) and ∼13.5 GPa (8YSZ-CNT reinforced), which is attributed to acquiescent nature and non-metallurgical bonding of CNT with MR. Indentation fracture toughness increased from 3.4 MPam 0.5 (for μ-Al2 O3 ) to a maximum of 5.4 MPam 0.5 (8YSZ- CNT reinforced) showing ∼57.7% improvement, which is due to crack termination at NR, retention of t-ZrO2 (∼3.3 vol%) crack bridging, and CNT pull-out toughening mechanisms. Modified fractal models affirmed that the introduction of bimodal microstructure (NR) i.e., nanometer-sized- Al2 O3, nanostructured 8YSZ and CNTs in the μ-Al2 O3 (MR) contributes ∼44.6% and ∼72% towards fracture toughness enhancement for A8Y and A8YC coatings. An enhanced contribution of nanostructured phases in toughening microstructured Al2 O3 matrix (in plasma sprayed A8YC coating) is established via modified fractal model affirming crack deflection and termination for potential TBC applications.